2008
DOI: 10.1186/1745-6215-9-5
|View full text |Cite
|
Sign up to set email alerts
|

Seminars may increase recruitment to randomised controlled trials: lessons learned from WISDOM

Abstract: Background: Recruiting patients to large randomised controlled trials (RCTs) in the primary care setting can be challenging. Research teams need to identify and utilise strategies that both maximise the efficiency of recruitment and minimise the burden on general practitioners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The overall acceptance rate in the UKCTOCS was similar to that seen in the colorectal cancer screening trial at Dundee and the WISDOM trial involving estrogen use after the menopause. 24 25 These rates were substantially higher than the 4.3% acceptance rate reported after a mass mailing of more than 3.4 million in the US systolic hypertension (SHEP) trial. 13 However, they were much lower than the 55% achieved in the UK FLEXISIG trial.…”
Section: Discussionmentioning
confidence: 90%
“…The overall acceptance rate in the UKCTOCS was similar to that seen in the colorectal cancer screening trial at Dundee and the WISDOM trial involving estrogen use after the menopause. 24 25 These rates were substantially higher than the 4.3% acceptance rate reported after a mass mailing of more than 3.4 million in the US systolic hypertension (SHEP) trial. 13 However, they were much lower than the 55% achieved in the UK FLEXISIG trial.…”
Section: Discussionmentioning
confidence: 90%
“…Although numbers are too small to draw conclusions, we do not have indications that the participation rate is higher in the hospitals that had a research nurse explaining the trial to the patient and her parent(s). Group seminars with potential participants may be a useful strategy for maximising recruitment (at least from general practices) [19]. For our trial, however, this would have been too complicated to carry out in practice, because there were only a couple of eligible patients per month, and they lived scattered over the whole country.…”
Section: Level Of the Patientmentioning
confidence: 99%
“…Recruitment to clinical trials in primary care can be challenging [ 1 ]. Recent papers in Trials have reported a variety of strategies to improve trial recruitment [ 2 - 4 ]. Drawing on the expanding field of health informatics, we report on a strategy to identify potential trial participants using routinely collected anonymised data that complements other approaches to this question [ 5 ].…”
Section: Introductionmentioning
confidence: 99%